2022-RA-1115-ESGO Evaluation of cervical dysplasia with NOVAprep-miR-CERVIX. (20th October 2022) - Kniazeva, Margarita; Zabegina, Lidia; Shalaev, Andrey; Koneva, Olga; Smirnova, Olga; Berlev, Igor; Malek, Anastasia
Abstract : Introduction/Background: Cervical cancer (CC) is one of the most common types of cancer and the fourth leading cause of cancer-related deaths in women. Cervical carcinogenesis is multistep process of the cervical dysplasia development and progression. Correct diagnostic and effective therapy of cervical dysplasia presents an important approach to reduce CC morbidity and mortality. MicroRNAs in cervical epithelium cells are considered as promising diagnostic markers of cervical dysplasia. MicroRNA-based diagnostic test-systems can provide a helpful addition to traditional diagnostic techniques. Methodology: NOVAprep-miR-CERVIX is a new test-system based on RT-qPCR analysis of six miRNAs (miR-21–5p; miR-29b-3p; miR-145–5p; miR-451a-5p; miR-1246–5p and miR-1290–3p) in material of cervical smear. Test-system includes quality of material control and control of enzymatic reaction efficacy. Machine learning based of random forest algorithm was applied for RT-qPCR results evaluation. Cervical smear samples were obtained from 226 women: 114 samples of normal epithelium and 112 samples of cervical epithelium with high-grad intraepithelial lesion (HSIL) or carcinoma in situ (CIS) as a result of cytological evaluation. Moreover, any of HSIL/CIS diagnosis was confirmed histologically. Results: The 38 samples from 216 (17.8%) did not pass quality controls and were excluded from analysis. NOVAprep-miR-CERVIX Index (miR-CERVIX-I varied from 0 to 1) was calculated on the base of results of six miRNA analysis for remaining 178 samples. Difference in miR-CERVIX-I was statistically significant in two groups of samples formed on the base of cytological/histological diagnosis ( figure 1 ). Normal condition of cervical epithelium (miR-CERVIX-I < 0.49) was diagnosed with sensitivity 79.2%, specificity 80.46%. HSIL was diagnosed with sensitivity 70.83%, specificity 97.22% (miR-CERVIX-I > 0.78). Moreover, intermediate value of miR-CERVIX-I (between 0.5 and 0.77) is supposed to reflect condition of low-grade intraepithelial dysplasia. Conclusion: NOVAprep-miR-CERVIX can be applied for cervical dysplasia diagnostic and management as a test system complimentary to standard methods.